2021
DOI: 10.1038/s41598-021-85641-4
|View full text |Cite|
|
Sign up to set email alerts
|

Optimum protein requirement of juvenile orange-spotted grouper (Epinephelus coioides)

Abstract: The purpose of subject was to explore the optimum protein requirement of juvenile grouper (Epinephelus coioides). In the test, 450 juveniles with an average weight (10.02 ± 0.22) g were randomly divided into six groups with triplicate, and were fed with 350, 400, 450, 500, 550 and 600 g/kg iso-lipid test diet twice 1 day for 8 weeks, respectively. The results showed that: (1) With the increase of protein level, the body weight gain rate and specific growth rate first increased and then reduced, while the feed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Therefore, the failure in application of formulated feed as a sole diet in commercial large yellow croaker farming in the past two decades may follow the story of largemouth bass (Huang et al, 2017). Compared with the other marine carnivorous fish species, the dietary protein requirement of large yellow croaker is similar to that of Korean rockfish, Sebastes schlegeli (509 g/kg crude protein, Kim et al, 2004), grouper, Epinephelus coioides (480-520 g/kg crude protein, Luo et al, 2004;Yan et al, 2021), and giant croaker, Nibea japonica (480 g/kg crude protein, Chai et al, 2013), but is higher than that of Japanese flounder, Paralichthys olivaceus (460-510 g/kg crude protein, Lee & Kim, 2005), cuneate drum, Nibea miichthioides (460 g/kg crude protein, Wang et al, 2006), and golden pompano, Trachinotus ovatus (450-490 g/kg crude protein, Wang et al, 2013). Duan et al (2001) reported that 105 g/kg crude lipid was optimal for growth of large yellow croaker, and the subsequent studies indicated that the optimal dietary lipid level was 104-122 g/kg for the fish weighing 7-10 g (Li et al, 2019;Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the failure in application of formulated feed as a sole diet in commercial large yellow croaker farming in the past two decades may follow the story of largemouth bass (Huang et al, 2017). Compared with the other marine carnivorous fish species, the dietary protein requirement of large yellow croaker is similar to that of Korean rockfish, Sebastes schlegeli (509 g/kg crude protein, Kim et al, 2004), grouper, Epinephelus coioides (480-520 g/kg crude protein, Luo et al, 2004;Yan et al, 2021), and giant croaker, Nibea japonica (480 g/kg crude protein, Chai et al, 2013), but is higher than that of Japanese flounder, Paralichthys olivaceus (460-510 g/kg crude protein, Lee & Kim, 2005), cuneate drum, Nibea miichthioides (460 g/kg crude protein, Wang et al, 2006), and golden pompano, Trachinotus ovatus (450-490 g/kg crude protein, Wang et al, 2013). Duan et al (2001) reported that 105 g/kg crude lipid was optimal for growth of large yellow croaker, and the subsequent studies indicated that the optimal dietary lipid level was 104-122 g/kg for the fish weighing 7-10 g (Li et al, 2019;Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hidalgo et al [57] and Fernández et al [58], α-amylase activity is more dependent on fish nutritional habits than the proteolytic activity, and this is further supported by the lack of effects on the proteolytic activity reported in gilthead seabream fed diets with different P/CH ratios [25][26][27]. However, studies in other fish species showed that higher dietary protein levels increased proteolytic activity [59][60][61][62]. In the present study, higher proteolytic activity in fish fed the diet with a higher protein content was also observed in the PC, but only in fish fed the PF-based diets.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum dietary protein, carbohydrate, and lipid levels for red spotted grouper were 508.3 g kg −1 (initial body weight = 7.88 ± 0.04 g), 76.4 g kg −1 (IBW = 7.79 ± 0.01 g), and less than 91.1 g kg −1 (IBW = 2.51 g), respectively [ 17 , 18 , 19 ]. Moreover, the optimal dietary protein requirements for orange-spotted grouper Epinephelus coioides were 480 (IBW = 10.7 ± 0.2 g), 521.84 (IBW = 10.02 ± 0.22 g) and 466.65 (IBW = 102.8 ± 1.02 g) g kg −1 reported by Luo et al (2004), Yan et al (2021) and Yan et al (2020), respectively [ 20 , 21 , 22 ]. Groupers need a high protein level (about 500 g kg −1 ) for optimum growth.…”
Section: Introductionmentioning
confidence: 96%